Allometric associations between body size, shape, and 100-m butterfly speed performance - Sammoud, S.; Nevill, A. M.; Negra, Y.; Bouguezzi, R.; Chaabene, H.; Hachana, Y. (The Journal of Sports Medicine and Physical Fitness, 2018)
BACKGROUND: This study aimed to estimate the optimal body size, limb-segment length, and girth or breadth ratios associated with 100-m butterfly speed performance in swimmers. METHODS: One-hundred-sixty-seven swimmers as subjects (male: N.=103; female: N.=64). Anthropometric measurements comprised height, body-mass, skinfolds, arm-span, upper-limb-length, upper-arm, forearm, hand-lengths, lower-limb-length, thigh-length, leg-length, foot-length, arm-relaxed-girth, forearm-girth, wrist-girth, thigh-girth, calf-girth, ankle-girth, biacromial and biiliocristal-breadths. To estimate the optimal body size and body composition components associated with 100-m butterfly speed performance, we adopted a multiplicative allometric log-linear regression model, which was refined using backward elimination. RESULTS: Fat-mass was the singularly most important whole-body characteristic. Height and body-mass did not contribute to the model. The allometric model identified that having greater limb segment length-ratio (arm-ratio = [arm-span]/[forearm]) and limb girth-ratio (girth-ratio = [calf-girth]/[ankle-girth]) were key to butterfly speed performance. A greater arm-span to forearm-length ratio and a greater calf to ankle-girth-ratio suggest that a combination of larger arm-span and shorter forearm-length and the combination of larger calves and smaller ankles-girth may benefit butterfly swim speed performance. In addition having greater biacromial and biliocristal breadths is also a major advantage in butterfly swimming speed performance. Finally, the estimation of these ratios was made possible by adopting a multiplicative allometric model that was able to confirm, theoretically, that swim speeds are nearly independent of total body size. CONCLUSIONS: The 100-m butterfly speed performance was strongly negatively associated with fat mass and positively associated with the segment length ratio (arm-span/forearm-length) and girth ratio (calf-girth)/(ankle-girth), having controlled for the developmental changes in age.